Indoor Air Quality. (July 2017) - Seguel, Joseph M.; Merrill, Richard; Seguel, Dana; Campagna, Anthony C.
Many health care providers are concerned with the role environmental exposures play in the development of respiratory disease. While most individuals understand that outdoor air quality is important to their health status, many are unaware of the detrimental effects indoor air pollution can potentially have on them. The Environmental Protection Agency (EPA) regulates both outdoor and indoor air quality. According to the EPA, indoor levels of pollutants may be up to 100 times higher than outdoor pollutant levels and have been ranked among the top 5 environmental risks to the public. There has been a strong correlation between air quality and health, which is why it is crucial to obtain a complete environmental exposure history from a patient. This article focuses on the effects indoor air quality has on the respiratory system. Specifically, this article will address secondhand smoke, radon, carbon monoxide, nitrogen dioxide, formaldehyde, house cleaning agents, indoor mold, animal dander, and dust mites. These are common agents that may lead to hazardous exposures among individuals living in the United States. It is important for health care providers to be educated on the potential risks of indoor air pollution and the effects it may have on patient outcomes. Health problems resulting from poor indoor air quality are not easily recognized and may affect a patient's health years after the onset of exposure.